2021
DOI: 10.3389/fpubh.2021.669070
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Frequent/Urgent Urination in Older Adults in China: A Multicenter, Cross-Sectional Study

Abstract: Background: Frequent/urgent urination is an event of multifactorial origin where involuntary leakage of urine occurs. Epidemiological study of this condition is of high importance due to its negative impact on the psychological, physical, and social well-being of the victims.Objective: This cross-sectional study aimed to investigate the prevalence of frequent/urgent urination in older adults in China.Method: In this study, a face-to-face questionnaire survey was conducted between April 2019 and August 2019 amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The output frequency results are tabulated in Table III. It is observed that as compared to the first pour the second pour of fluid produced a noticeable change in the output frequency making it feasible to detect intermittent urination events which is a key predictor to timely diagnose several diseases like UTI and bladder inflammation [48]. It is observed that both silver and carbon printed capacitive sensors yield similar behavior in all the measurement scenarios except the level of output frequency which has been higher for the carbon sensor because of its higher sheet resistance.…”
Section: Resultsmentioning
confidence: 91%
“…The output frequency results are tabulated in Table III. It is observed that as compared to the first pour the second pour of fluid produced a noticeable change in the output frequency making it feasible to detect intermittent urination events which is a key predictor to timely diagnose several diseases like UTI and bladder inflammation [48]. It is observed that both silver and carbon printed capacitive sensors yield similar behavior in all the measurement scenarios except the level of output frequency which has been higher for the carbon sensor because of its higher sheet resistance.…”
Section: Resultsmentioning
confidence: 91%
“…Five of the 20 articles focusing exclusively on the community setting suggested that age was a significant demographic risk factor [ 36 , 46 , 58 , 60 , 65 ]. Five community-based studies documented urgency UI (UUI) as the most common established UI type [ 31 , 32 , 65 , 67 , 68 ], while stress UI (SUI) was less prevalent [ 42 , 46 , 47 , 69 ]. Physiological factors associated with UUI included increased fat mass (participants’ mean total fat mass = 24 kg), greater waist circumference (mean waist circumference = 100.6 cm) and decreased grip strength (5% or greater decrease in maximum grip strength) [ 31 ].…”
Section: Results/evidence Synthesismentioning
confidence: 99%
“…In this longitudinal study, higher fat mass percent and greater waist circumference were marginally associated with prevalent UI at least monthly, but strongly associated with prevalent UI at least weekly [ 31 ]. An association between UUI and medical factors/diseases (diabetes, heart disease, anxiety, depression, constipation, and brain injury) was found in a recent community-based study [ 32 ]. Gerst et al .…”
Section: Results/evidence Synthesismentioning
confidence: 99%
“…The independent group showed an increase in Toilet_Frequency compared to the community elderly group, which may have led to increases in Toilet_Times and non-SB_Toilet_Times. Urinary frequency may increase with age and dysfunction (38, 39), and the independent group may need frequent toileting behavior due to declines in urinary function. However, the non-independent group did not show a signi cantly higher frequency of toileting behavior than the community elderly group.…”
Section: Physical Activity and Toileting Behaviormentioning
confidence: 99%